Analisis Pengaruh Struktur Modal, Struktur Aktiva, Dan Total Assets Turnover (TATO) Terhadap Nilai Perusahaan pada Perusahaan Subsektor Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Juliani, Juliani; Purnamawati, Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to analyze the effect of capital structure, asset structure, and total asset turnover either partially or simultaneously on firm value during 2016-2020. This study uses quantitative research using secondary data obtained from Coal Mining Sub-Sector Companies listed on the Indonesia Stock Exchange. This research was conducted in a quantitative descriptive manner using secondary data obtained from the financial statements of the Indonesia Stock Exchange. This study has a population of 22 with 18 samples. The sampling technique used purposive sampling method by considering certain criteria. The analysis technique used in this research is multiple linear regression. The variables used in this study are capital structure, asset structure, and total assets turnover as independent variables, firm value as the dependent variable. The results of the t-test show that the Long-Term Debt to Equity Ratio has a negative and insignificant effect, the Fixed Asset Ratio has a positive and insignificant effect, and the Total Asset Turnover has a positive and significant effect. The results of the F test show that the Long-Term Debt to Equity Ratio, Fixed Asset Ratio, and Total Asset Turnover simultaneously have a significant positive effect on firm value.